Multiparametric MRI for early identification of therapeutic response in recurrent glioblastoma treated with immune checkpoint inhibitors. Issue 11 (20th March 2020) - Song, Joseph; Kadaba, Priyanka; Kravitz, Amanda; Hormigo, Adilia; Friedman, Joshua; Belani, Puneet; Hadjipanayis, Constantinos; Ellingson, Benjamin M; Nael, Kambiz
Abstract: Background: Physiologic changes quantified by diffusion and perfusion MRI have shown utility in predicting treatment response in glioblastoma (GBM) patients treated with cytotoxic therapies. We aimed to investigate whether quantitative changes in diffusion and perfusion after treatment by immune checkpoint inhibitors (ICIs) would determine 6-month progression-free survival (PFS6) in patients with recurrent GBM. Methods: Inclusion criteria for this retrospective study were: (i) diagnosis of recurrent GBM treated with ICIs and (ii) availability of diffusion and perfusion in pre and post ICI MRI (iii) at ≥6 months follow-up from treatment. After co-registration, mean values of the relative apparent diffusion coefficient (rADC), K trans (volume transfer constant), Ve (extravascular extracellular space volume) and Vp (plasma volume), and relative cerebral blood volume (rCBV) were calculated from a volume-of-interest of the enhancing tumor. Final assignment of stable/improved versus progressive disease was determined on 6-month follow-up using modified Response Assessment in Neuro-Oncology criteria. Results: Out of 19 patients who met inclusion criteria and follow-up (mean ± SD: 7.8 ± 1.4 mo), 12 were determined to have tumor progression, while 7 had treatment response after 6 months of ICI treatment. Only interval change of rADC was suggestive of treatment response. Patients with treatment response (6/7: 86%) had interval increased rADC, while 11/12 (92%) with tumor progression had decreased rADC ( P = 0.001). Interval change in rCBV, K trans, Vp, and Ve were not indicative of treatment response within 6 months. Conclusions: In patients with recurrent GBM, interval change in rADC is promising in assessing treatment response versus progression within the first 6 months following ICI treatment. Key Points:  In recurrent GBM treated with ICIs, interval change in rADC suggests early treatment response.  Interval change in rADC can be used as an imaging biomarker to determine PFS6.  Interval change in MR perfusion and permeability measures do not suggest ICI treatment response.